New oligothienyl-imidazo-phenanthroline chromophores for NLO applications - Batista, Rosa Maria Ferreira (2008)
A new series of oligothienyl-imidazo-phenanthrolines 3 were synthesised in good to excellent yields by condensation of 5,6-phenantroline-dione 2 with formyl-thiophene derivatives 1 in the presence of ammonium acetate in glacial acetic acid. Furthermore, their solvatochromism and molecular optical nonlinearities were determined and comparatively studied. The experimental results indicate that phenanthrolines 3, due to their moderate solvatochromic properties and good optical nonlinearities, could be used as suitable probes for the determination of solvent polarity and as nonlinear optical materials.